2017
DOI: 10.21548/38-2-2127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sun, Oven and Freeze-Drying on Anthocyanins, Phenolic Compounds and Antioxidant Activity of Black Grape (Ekşikara) (Vitis vinifera L.)

Abstract: The aim of this study was to determine whether a change occurs in the phenolic compounds and antioxidant activity of grapes after drying. Grapes pre-treated with potassium hydroxide solution were dried using three different drying methods, namely freeze drying, oven drying and sun drying. The effectiveness of the drying methods was evaluated in terms of total phenolic content, antioxidant activity (ABTS, FRAP and DPPH), individual phenolics and anthocyanins. Losses in total phenolic content of the grapes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 39 publications
4
37
2
1
Order By: Relevance
“…The highest value for total phenolic content found to be 20.21 mg/g DW in fresh grapes, but this value in the freeze-, oven-and sun-dried samples continued to decrease. The values of DPPH and ABTS antioxidant activities in fresh grapes determined as 66.07 mmol TE/kg DW and 137.65 mmol TE/kg DW (29). Total phenolic compounds of red grape varieties examined by Correia and Jordão found to be average 1341.0 mg/L, and antioxidant capacities determined varying from 3.96 to 32.96 mm/L Fe(II) (30).…”
Section: Resultsmentioning
confidence: 90%
“…The highest value for total phenolic content found to be 20.21 mg/g DW in fresh grapes, but this value in the freeze-, oven-and sun-dried samples continued to decrease. The values of DPPH and ABTS antioxidant activities in fresh grapes determined as 66.07 mmol TE/kg DW and 137.65 mmol TE/kg DW (29). Total phenolic compounds of red grape varieties examined by Correia and Jordão found to be average 1341.0 mg/L, and antioxidant capacities determined varying from 3.96 to 32.96 mm/L Fe(II) (30).…”
Section: Resultsmentioning
confidence: 90%
“…Typha orientalis which recorded the highest amount of moisture loss (93.6%) showed more moisture loss in 2017 compared to 2019 ( P < 0.05). Freeze‐drying has been reported as a less aggressive drying method (de Torres et al , ; Çoklar & Akbulut, ) due to its ability to prevent loss of volatile polyphenols and potential antioxidants, thus maintaining the TPC of the samples during processing (Mediani et al , ). Our results indicate that freeze‐drying in addition to its less aggressiveness in dehydrating the samples is also an efficient moisture remover, consistent with the findings of Puranik et al () who after a comparative study of different drying techniques on the quality of garlic, concluded that freeze‐dried samples had maximum water loss, than fluidised bed drying, oven‐drying and microwave heating methods.…”
Section: Resultsmentioning
confidence: 99%
“…The drying temperature of the oven also affects the concentration of cyanidin derivatives; drying sour cherries at 50 • C reduced cyanidin-3-glucoside, compared to fresh ones [31]. In addition, extraction of the phenolic compounds affected the reduction in particle size, solvent types used for extraction, and the porosity of the dried samples [32].…”
Section: Cyanidin Derivatives In Mango-natal Plum Fruit Leathersmentioning
confidence: 99%
“…Thus, on this note, the sugar content in Natal-plum fruit leather snack may not offset any potential benefits of bioactive components. In the presence of hydrophilic groups (such as those from pectin, fibre, and other soluble solids), drying can take longer, but longer drying times are associated with degradation of phytochemicals [32].…”
Section: Proximate Analysis Of Mango-natal Plum Fruit Leather (Mn2)mentioning
confidence: 99%